Cover Image, Volume 30, Issue 10. (13th September 2017) - Roberts, Thomas A.; Price, Anthony N.; Jackson, Laurence H.; Taylor, Valerie; David, Anna L.; Lythgoe, Mark F.; Stuckey, Daniel J.
Abstract : The cover image, by Thomas A. Roberts et al., is based on the Research Article Direct comparison of high‐temporal‐resolution CINE MRI with Doppler ultrasound for assessment of diastolic dysfunction in mice, DOI:10.1002/nbm.3763 .